WATER AND DAMS A POLITICAL AND A LYRICAL APPROACH: ARUNDHATI ROY AND ANNE MICHAELS - Concilio, Carmen (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2016)
This essay starts by quoting Aesop’s fable of “The Wolf and the Lamb” as an allegory of conflicts related to the control and distribution of water in our contemporary world. Megadams are among the controlling factors not only as far as distribution of water is concerned, but also as far as the mere life of people is concerned. To control water means to control people’s life. And megadams have become the subject matter of recent literature. The aim of this essay is to analyse different stylistic ways of approaching the themes of dams, water and human rights, through the works of a well-known writer-activist, Arundhati Roy, and a Canadian poet and novelist, Anne Michaels.